Propuesta para el aprovechamiento del aluminio PG, proveniente de aguas residuales de producción de hidrogeles en la planta Antonio Ricaurte Fexar Indumil (2017)
The recovery of aluminium PG, that is used in the production of explosive-type Hydrogel and sismigel as raw material for the production of aluminium sulphate that can be used as a flocculant to water treatment it is proposed. During this development takes into account the characteristics of the wash water coming out of hydrogels production workshops and tellex, to know its content of aluminum and other components that affect the process, is carried out on an experimental basis a physical separation based on particle size of aluminum 2µm which facilitates the filtration, this yields a product recovered with a high content of penrite, which is discarded.